Noninstitutional births and newborn care practices among adolescent mothers in Bangladesh - Rahman, Mosiur Mosiur; Haque, Syed Emdadul Mdadul; Zahan, Sarwar; Islam, Ohidul (© 2011 JOGNN - Journal of Obstetric, Gynecologic, and Neonatal Nursing, 2016)
This article was published in the International Journal of Educational Development [© 2011 AWHONN, the Association of Women's Health, Obstetric and Neonatal Nurses] and the definite version is available at : http://doi.org/10.1111/j.1552-6909.2011.01240.x. The Journal's website is at: http://www.jognn.org/article/S0884-2175(15)30542-6/abstract